2013
DOI: 10.1021/jp402903t
|View full text |Cite
|
Sign up to set email alerts
|

Ab Initio Chemical Kinetics for H + NCN: Prediction of NCN Heat of Formation and Reaction Product Branching via Doublet and Quartet Surfaces

Abstract: The reaction of NCN with H atoms has been investigated by ab initio MO and RRKM theory calculations. The mechanisms for formation of major products on the doublet and quartet potential energy surfaces have been predicted at the CCSD(T) level of theory with the complete basis set limit. In addition, the heat of formation for NCN predicted at this rigorous level and those from five isogyric reactions are in close agreement with the best value based on the isodesmic process, (3)CCO + N2 = (3)NCN + CO, 109.4 kcal/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
50
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(58 citation statements)
references
References 48 publications
7
50
1
Order By: Relevance
“…Knowledge of the subsequent reactions of the NCN radical has improved con- siderably in recent years, owing to a large degree to the shock tube work of Friedrichs and coworkers who determined rate constants for several of the NCN reactions, i.e., NCN + M (R7) [83], NCN + H [78], NCN + O (R9) [83], NCN + O 2 (R13) [85], and NCN + NO (R14) [86]. In addition, Lin and coworkers have studied theoretically a number of reactions, including NCN + H [92], NCN + O [84], NCN + OH [93] and NCN + O 2 [94]. Very recently, Klippenstein et al [82] reported a theoretical study of NCN + H and NCN + OH.…”
Section: Reaction Subset For Prompt No Formationmentioning
confidence: 99%
“…Knowledge of the subsequent reactions of the NCN radical has improved con- siderably in recent years, owing to a large degree to the shock tube work of Friedrichs and coworkers who determined rate constants for several of the NCN reactions, i.e., NCN + M (R7) [83], NCN + H [78], NCN + O (R9) [83], NCN + O 2 (R13) [85], and NCN + NO (R14) [86]. In addition, Lin and coworkers have studied theoretically a number of reactions, including NCN + H [92], NCN + O [84], NCN + OH [93] and NCN + O 2 [94]. Very recently, Klippenstein et al [82] reported a theoretical study of NCN + H and NCN + OH.…”
Section: Reaction Subset For Prompt No Formationmentioning
confidence: 99%
“…Whatever channel (d-f) of reaction (2) was assumed, simulated NO profiles are identical to each other. However, considering channel (2d), implementation of reactions (12)(13)(14)(15)(16)(17)(18)(19) could be removed since HCN and NH species are already declared in GDF. 13 In that case, simulated NO profiles would be identical to those obtained with the original GDF mechanism.…”
Section: Flame Modelingmentioning
confidence: 99%
“…They reported RRKM and TST studies for the most important bimolecular NCN reactions NCN + O 2 , 16 O, 17 OH 18 and H 19 as well as for the NCN forming reaction CH + N 2 . 6,19 From the experimental point of view, most direct rate constant measurements of NCN reactions have been accomplished over the past few years in the shock tube laboratory of the authors (N.F. and G.F.).…”
Section: Introductionmentioning
confidence: 99%
“…In combustion chemistry, the kinetics of the cyanonitrene radical, NCN, has recently attracted attention [4][5][6][7][8][9][10][11] because NCN is considered an important intermediate in the formation of so-called prompt NO in hydrocarbon flames under fuel-rich conditions [12][13][14][15][16][17][18][19][20]. Cyanonitrene is a linear diradical with a 3 − g electronic ground state [21,22] and was shown to be formed under combustion conditions in the spin-allowed reaction CH(…”
Section: Introductionmentioning
confidence: 99%